2021
DOI: 10.1016/j.crmicr.2021.100087
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of Photobacterium species from terrestrial and marine habitats

Abstract: Highlights Photobacteria exploit horizontal gene transfer for niche adaptation. P. phosphoreum divides into two subspecies with no correlation to isolation origin or metabolism. P. phosphoreum has wider tools for stress response and antimicrobial activity. P. iliopiscarium divides in two clades (marine/terrestrial) with distinct environmental adaptation. P. car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 95 publications
(134 reference statements)
2
7
0
Order By: Relevance
“…Unlike P. phosphoreum , showing no differential detection, results suggest that P. carnosum has a higher sensitivity and, therefore, has an earlier response to stress. This was also supported by previously predicted higher sensitivity to oxidative stress (Fuertes-Perez et al, 2021 ) and the demonstrated sensitivity to other types of stress such as high pressure, temperature, and salt concentration (Hilgarth et al, 2018b ; Hauschild et al, 2020 ).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Unlike P. phosphoreum , showing no differential detection, results suggest that P. carnosum has a higher sensitivity and, therefore, has an earlier response to stress. This was also supported by previously predicted higher sensitivity to oxidative stress (Fuertes-Perez et al, 2021 ) and the demonstrated sensitivity to other types of stress such as high pressure, temperature, and salt concentration (Hilgarth et al, 2018b ; Hauschild et al, 2020 ).…”
Section: Resultssupporting
confidence: 81%
“…The synthesis of an additional proton-translocating NADH dehydrogenase complex by P. phosphoreum might influence the efficiency of the respiratory chain and explain, to some extent, the aerobically faster growth of the species in comparison to P. carnosum . As predicted before by Fuertes-Perez et al ( 2021 ), they use both the non-electrogenic and sodium-translocating version of Complex I, which is in agreement with the sodium requirement of these bacteria (Hilgarth et al, 2018a , b ). Additionally, P. phosphoreum also synthesizes the proton-translocating version.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations